2014
DOI: 10.1091/mbc.e13-10-0631
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive protein–protein interactome for yeast PAS kinase 1 reveals direct inhibition of respiration through the phosphorylation of Cbf1

Abstract: PAS kinase is a conserved sensory protein kinase required for glucose homeostasis. The interactome for yeast PAS kinase 1 (Psk1) is identified, revealing 93 binding partners. Evidence is provided for in vivo phosphorylation of Cbf1 and subsequent inhibition of respiration, supporting a role for Psk1 in partitioning glucose for cell growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 71 publications
(112 reference statements)
3
27
0
Order By: Relevance
“…As mentioned, SNF1 is the master and commander of the fermentation/respiration switch in yeast and is required for the activation of Psk1 by nonglucose carbon sources ( Grose et al ., 2007 ). We recently retrieved Snf1 and two of its subunits (Gal83 and Sip2) from a large-scale screen for Psk1 binding partners ( DeMille et al ., 2014 ), suggesting that this activation is direct. To test for direct phosphorylation, in vivo Psk1 activity and phosphorylation state were monitored in response to SNF1 activation or depletion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned, SNF1 is the master and commander of the fermentation/respiration switch in yeast and is required for the activation of Psk1 by nonglucose carbon sources ( Grose et al ., 2007 ). We recently retrieved Snf1 and two of its subunits (Gal83 and Sip2) from a large-scale screen for Psk1 binding partners ( DeMille et al ., 2014 ), suggesting that this activation is direct. To test for direct phosphorylation, in vivo Psk1 activity and phosphorylation state were monitored in response to SNF1 activation or depletion.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the phosphorylation and activation of Psk1 is direct, we performed in vitro phosphorylation assays. Kinase-dead Psk1 (D1230A; DeMille et al ., 2014 ) was purified and subjected to in vitro kinase assays with purified Snf1. PAS kinase is known to autophosphorylate in vitro ( Rutter et al ., 2001 ), making the kinase-dead mutant vital to ensure Snf1-dependent phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies revealed that a signaling cascade upstream of mTORC1 that includes the nutrient‐sensing kinases, AMPK/SNF1 and PSK1, is implicated in the ATXN2‐dependent inhibition of mTOR. Both yeast two‐hybrid and biochemical co‐purification studies have validated that PSK1, a yeast homolog of PAS kinase, associates with ATXN2 (DeMille et al, ). Energy‐deprived growth conditions (e.g., a nonglucose carbon source) promote the AMPK/SNF1‐dependent phosphorylation and activation of PSK1, which then phosphorylates ATXN2 and enhances the sequestration of mTOR (DeMille et al, ; Figure ).…”
Section: Cellular Functions Of Ataxin‐2mentioning
confidence: 99%
“…The glycogen synthase Gsy2p have also been reported as a PSK kinase substrate (Grose, Smith, Sabic, & Rutter, ; Hao et al, ; Rutter, Probst, & McKnight, ; Smith & Rutter, ). Analysis of the protein–protein interactome (i.e., complete map of protein interactions) for PSK1 showed that the PSKs paralogs are involved in cell growth/proliferation, glucose allocation, vacuole function, and stress tolerance (DeMille et al, ; DeMille et al, ). In other words, these two PAS kinases seem to regulate a broad range of metabolic processes, such as nutrient partitioning, glucose utilization, gene expression as well as promotion of protein synthesis.…”
Section: Introductionmentioning
confidence: 99%